A Mediated-Approach to Disrupting SpeA-TCR Interactions for the Treatment of Streptococcus pyogenes Infection - Al-Sabaawi, Rana; Al-Rrassam, Zeyad; Altobje, Mahmood (Trends in Sciences, 2025)
Streptococcus pyrogenic exotoxin A (SpeA) has been implicated in several S. pyogenes illnesses, including invasive and non-invasive infections. The main investigation of this study explores methods to use gRNA SpeA-Cas9 both to disrupt the SpeA-TCR interaction and decrease S. pyogenes pathogenicity. This research aims to develop and verify protective gRNA sequences as well as conduct analyzes of their structural characteristics and thermal behavior while assessing potential therapeutic possibilities. The gRNA SpeA sequence, 2D and 3D structures were predicted using the CRISPRDB, SimRNA 2.0, and RNAfold services, respectively. Geneious Prime was utilized to finish the PCR and clone gRNA-Cas9 into pCRII-TOPO. FUpred was utilized to detect the boundary domains. CGR approaches were used to map a part of the target sequence of gRNA SpeA over the whole S. pyogenes genome. The HDOCK server was used to dock SpeA and TCR molecules. EcoRI is the most suitable restriction enzyme for gRNA SpeA-Cas9 transformation. The target sequence (ACGGAGG) was determined in the A20 strain complete genome map. The optimum biochemical and biophysical properties of gRNA SpeA-Cas9 were estimated. Model 2 is appropriate for positioning the SpeA gRNA between the docking proteins (SpeA-TCR). S. pyogenes loses its virulence and its capacity to induce infection when SpeA begins to attach less strongly to host cell receptors. An effective path toward innovative treatment options is provided by the gRNA-based strategy. There is a chance that gRNA will change how much SpeA and TCR interact molecularly. This study shows CRISPR-Cas9 targeted against SpeA results in a reduction of SpeA’s specificity for TCR receptors which successfully controls immune cell overreactivity. Research reveals that targeting SpeA with CRISPR-Cas9 represents an appealing therapeutic solution to fight S. pyogenes infections as well as decrease their dangerous outcomes. HIGHLIGHTS SpeA has been implicated in a range of S. pyogenes diseases. SpeA is a secreted polypeptide, that identifies antigens that escape the immune system. Geneious Prime was utilized to finish the PCR and clone gRNA-Cas9 into pCRII-TOPO. The target sequence (ACGGAGG) was determined in the A20 strain complete genome map. GRAPHICAL ABSTRACT